Comparative study of the effect of intramyometrial carbetocin injection and rectal misoprostol on blood loss during myomectomy operations - Ashraf H Mohamed; Ahmed M Saeed; Mohamed F Taha (Wolters Kluwer Medknow Publications, 2021)
Background and aim Investigating the influence of intramyometrial carbetocin injections and rectal misoprostol on bleeding throughout myomectomy surgeries. Fibroids are firm benign tumors consisting of smooth muscle cells and fibrous connective tissues. Benign uterine leiomyomas (fibroids) are the commonest pelvic tumor in females, impacting 20-40% of all women, over the age of 35 and 50% of African-American women. This work aims to compare the effectiveness of intramyometrial carbetocin injections and rectal misoprostol on blood-loss amounts throughout myomectomy surgeries. Patients and methods A prospective randomized comparative study was performed on 120 females having myoma(s) recruited from the clinic. The 120 study participants were divided into three groups: group I involved 40 women who received intramyometrial injection of 100 µg of carbetocin, group II involved 40 women who received 400 µg of misoprostol, and group III involved 40 women who received nothing during the myomectomy operation. Results The mean blood loss was more in group III in comparison with misoprostol (group II) in comparison with carbetocin (group I) with a statistically significant difference among the three groups, it was 177.43±21.25 ml in group I, 238.00±43.87 ml in group II, and 288.00±29.72 ml in group III. Conclusion The usage of intramyometrial carbetocin injections throughout abdominal myomectomy surgery is more efficient in reducing the blood loss than the usage of rectal misoprostol than using nothing at all.